2013
DOI: 10.1073/pnas.1308998110
|View full text |Cite
|
Sign up to set email alerts
|

Paternally expressed genes predominate in the placenta

Abstract: The discovery of genomic imprinting through studies of manipulated mouse embryos indicated that the paternal genome has a major influence on placental development. However, previous research has not demonstrated paternal bias in imprinted genes. We applied RNA sequencing to trophoblast tissue from reciprocal hybrids of horse and donkey, where genotypic differences allowed parent-of-origin identification of most expressed genes. Using this approach, we identified a core group of 15 ancient imprinted genes, of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
147
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(156 citation statements)
references
References 49 publications
(53 reference statements)
8
147
1
Order By: Relevance
“…They went on to describe a mathematical model that corroborated these ideas. The horse-donkey hybrid data in Wang et al (2013) may fit better with this version of the hypothesis.…”
Section: Maternal-fetal Co-adaptationmentioning
confidence: 86%
See 3 more Smart Citations
“…They went on to describe a mathematical model that corroborated these ideas. The horse-donkey hybrid data in Wang et al (2013) may fit better with this version of the hypothesis.…”
Section: Maternal-fetal Co-adaptationmentioning
confidence: 86%
“…These authors then argued that this directional bias was consistent with data from the mouse, in which all genes known to be imprinted in the placenta but not elsewhere are maternally expressed (Ferguson-Smith et al, 2006;Wagschal and Feil, 2006). More recent data from horse-donkey hybrids, however, show an overabundance of paternally expressed imprinted genes in the equine placenta (Wang et al, 2013), which clearly does not fit with this prediction. Moreover, the model implies that imprinting should be found outside mammals, in taxa with strong parent-offspring interactions, and that in taxa where paternal care was important paternal expression would be favoured for the genes involved in this interaction.…”
Section: Dominance Modificationmentioning
confidence: 92%
See 2 more Smart Citations
“…Other studies have used placenta transcriptomes of several equines to study parent of origin effects and genetic imprinting, where the fetus inherits genes from either the mother or the father [31,32]. One study compared placental transcriptomes of horses, donkeys and their crosses (mules and hinnys) and found that a majority of the genes that were significantly different were paternally expressed, showing that the father's size has some influence in determining the size of the fetus [31]. Placental transcriptomics has also identified novel splice variants that are processed differently in various eutharian species.…”
Section: Comparative Placental Transcriptomicsmentioning
confidence: 99%